2011
DOI: 10.1105/tpc.110.079657
|View full text |Cite
|
Sign up to set email alerts
|

Phloem-Specific Expression of Yang Cycle Genes and Identification of Novel Yang Cycle Enzymes inPlantagoandArabidopsis   

Abstract: The 5-methylthioadenosine (MTA) or Yang cycle is a set of reactions that recycle MTA to Met. In plants, MTA is a byproduct of polyamine, ethylene, and nicotianamine biosynthesis. Vascular transcriptome analyses revealed phloem-specific expression of the Yang cycle gene 5-METHYLTHIORIBOSE KINASE1 (MTK1) in Plantago major and Arabidopsis thaliana. As Arabidopsis has only a single MTK gene, we hypothesized that the expression of other Yang cycle genes might also be vascular specific. Reporter gene studies and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
82
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 65 publications
1
82
1
Order By: Relevance
“…We had previously shown that MTI1 and DEP1 complemented the growth reduction of yeast mutants defective in the conversion of MTR1-P to MTRu1-P or of MTRu-1-P to DHKMP (Fig. 1A) on medium with MTA as sole S source (Pommerrenig et al, 2011). To analyze the function of both enzymes also in planta, we isolated mti1 and dep1 mutants and used them for growth assays on agar medium containing MTA or on hydroponic culture with different levels of S supply.…”
Section: Mti1 and Dep1 Are Met Cycle Unigenes In Arabidopsismentioning
confidence: 99%
See 4 more Smart Citations
“…We had previously shown that MTI1 and DEP1 complemented the growth reduction of yeast mutants defective in the conversion of MTR1-P to MTRu1-P or of MTRu-1-P to DHKMP (Fig. 1A) on medium with MTA as sole S source (Pommerrenig et al, 2011). To analyze the function of both enzymes also in planta, we isolated mti1 and dep1 mutants and used them for growth assays on agar medium containing MTA or on hydroponic culture with different levels of S supply.…”
Section: Mti1 and Dep1 Are Met Cycle Unigenes In Arabidopsismentioning
confidence: 99%
“…On the basis of an expression analysis of MTI1 and DEP1 in rosette leaves (Pommerrenig et al, 2011), we used reporter lines carrying promoter-gene-GFP and promoter-gene-GUS fusions of MTI1 and DEP1 for a more comprehensive expression analysis. These analyses revealed tissue-specific and overlapping localization patterns of MTI1 and DEP1.…”
Section: Mti1 and Dep1 Are Cytosolic Enzymes Localized In Vascular Anmentioning
confidence: 99%
See 3 more Smart Citations